2003
DOI: 10.1007/s10350-004-6611-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined Seton Placement, Infliximab Infusion, and Maintenance Immunosuppressives Improve Healing Rate in Fistulizing Anorectal Crohn's Disease

Abstract: Selective seton placement combined with infliximab infusion and maintenance immunosuppressives resulted in complete healing in 67 percent of Crohn's patients with perianal fistula and partial healing in 19 percent. Relapse was successfully treated with repeat infusion. Concomitant rectovaginal fistula was a poor prognostic indicator for successful infliximab therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
133
2
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(155 citation statements)
references
References 22 publications
6
133
2
14
Order By: Relevance
“…Female gender, complex fistula formation, active intestinal and rectal diseases were reported as factors independently associated with failure of combined treatment [16,17]. Any factor, which significantly related to complete response, could not be found in the study.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Female gender, complex fistula formation, active intestinal and rectal diseases were reported as factors independently associated with failure of combined treatment [16,17]. Any factor, which significantly related to complete response, could not be found in the study.…”
Section: Discussioncontrasting
confidence: 41%
“…In our opinion, surgeon would be aware of complex or multiple fistulas owing to preoperative MRI, and it indirectly increases the success of the treatment. [16] 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a complex fistula is located high (high transsphincteric, extrasphincteric or suprasphincteric), may be associated with pain, can potentially involve multiple external openings, and may be associated with rectovaginal fistula and/or anorectal stricture [6]. This is a clinically important differentiation, because several studies have shown better outcomes for patients with simple fistula tracts [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ineffective or inappropriate treatment of perianal fistula may lead to recurrence of the fistula or can result in the fistula progressing from simple to complex form [17]. Complex fistulas are more difficult to treat, have decreased healing rates, and are associated with less successful outcomes [7][8][9][10]. For these reasons, it would be very important to have predictors of the response of perianal fistulas to antibiotics.…”
Section: Introductionmentioning
confidence: 99%